2022
DOI: 10.3389/fphar.2022.873150
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Alleviates Intestinal Barrier Dysfunction via the AKT-GSK3β-β-Catenin Pathway in Peritoneal Dialysis

Abstract: Background and aims: Long-term peritoneal dialysis (PD) causes intestinal dysfunction, including constipation, diarrhea, or enteric peritonitis. However, the etiology and pathogenesis of these complications are still unclear and there are no specific drugs available in the clinic. This study aims to determine whether Astragaloside IV (AS IV) has therapeutic value on PD-induced intestinal epithelial barrier dysfunction in vivo and in vitro.Methods: We established two different long-term PD treatment mice models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…41 However, since GSK-3β was a hub gene of other signaling pathways such as PI3K/Akt, NOTCH, and so on, 42,43 there would be some crosstalk between these pathways, resulting in similar trends in the expression levels of GSK-3β as β-catenin and p-GSK-3β. [44][45][46] This suggested that when the Wnt signaling pathway was unobstructed, BM could activate Wnt to promote wound healing. Conversely, when Wnt was blocked, the potential role of BM in proliferation was significantly reduced.…”
Section: Activation Of Gsk-3β/β-catenin Signaling Axismentioning
confidence: 99%
“…41 However, since GSK-3β was a hub gene of other signaling pathways such as PI3K/Akt, NOTCH, and so on, 42,43 there would be some crosstalk between these pathways, resulting in similar trends in the expression levels of GSK-3β as β-catenin and p-GSK-3β. [44][45][46] This suggested that when the Wnt signaling pathway was unobstructed, BM could activate Wnt to promote wound healing. Conversely, when Wnt was blocked, the potential role of BM in proliferation was significantly reduced.…”
Section: Activation Of Gsk-3β/β-catenin Signaling Axismentioning
confidence: 99%
“…Notably, traditional Chinese medicine (TCM) offers a unique approach to the treatment of complex chronic diseases. It has been shown that TCMs such as astragalus, rhubarb, safflower and curcumin exert significant therapeutic effects on peritoneal injury as well as regulating inflammation and inhibiting abnormal ECM accumulation [123][124][125][126]. And SCs pretreated with TCMs have been proven to play a therapeutic role in many diseases [127,128].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…AS-IV prevents tight junctions (TJs) disruption and intestinal barrier damage by inhibiting activation of RhoA/NLRP3 inflammatory vesicle signaling in an in vivo cecal ligation and puncture (CLP)-induced sepsis model and an in vitro Lipopolysaccharide (LPS)-primed Caco-2 monolayer barrier model [ 27 ]. AS-IV promotes the phosphorylation level of AKT, inhibits GSK-3β activity, leads to nuclear translocation and accumulation of β-catenin, improves cell viability, and promotes the expression of TJ proteins and wound healing to alleviate Peritoneal Dialysis (PD)-associated intestinal dysfunction [ 28 ]. Given that AS-IV plays an important role in the repair of barrier function in vivo, we sought to explore the potential impact of the administration of AS-IV on barrier function in dextran sodium sulfate (DSS)-induced colitis mice, and whether PI3K/AKT plays a role in it.…”
Section: Introductionmentioning
confidence: 99%